Influence of sodium content on the thermal behavior of low vacancy Prussian white cathode material. Issue 11 (3rd March 2020) - Ojwang, Dickson O.; Häggström, Lennart; Ericsson, Tore; Ångström, Jonas; Brant, William R.
Abstract : Sodium content dictates the thermal stability, decomposition temperature and hydration degree of Prussian white. Abstract : Rechargeable sodium-ion batteries are the most attractive substitutes for lithium-ion batteries in large-scale energy storage devices due to wide spread reserves and low-cost of sodium resources and the similarities between sodium and lithium chemistry. However, finding a suitable cathode material is still a hurdle to be overcome. To date, Prussian white (PW), Na x Fe[Fe(CN)6 ] y · n H2 O has stood out as one of the most promising Na-host materials due to its low cost, facile synthesis and competitive electrochemical capacity. Despite this, there are concerns that this material will thermally decompose at relatively low temperatures to form cyanogen gas, which is a safety hazard. Thus, low vacancy Na x Fe[Fe(CN)6 ] y · n H2 O ( x = 1.5, 1, 0.5 and 0) has been synthesized, and the influence of x on its thermal behavior systematically investigated. It is demonstrated that the thermal decomposition temperature, water content and moisture sensitivity of the samples strongly depend on the sodium content. The sample with x = 1.5 is found to be the most thermally stable and has the highest water content under the same experimental conditions. In addition, the sodium-rich samples ( x = 1.5, 1 and 0.5) have higher surface water than the sodium-deficient one ( x = 0). The local structure for this sample is also very different to the sodium-rich ones. Our findings offer new insights into the profound implications of proper material handling and safer operating conditions for practical Na-ion batteries and may be extended to analogous systems.